Answer:
x = -0.47, x = 2.14
Explanation:
Quadratic formula is my favorite!!
Let's first take that four over to the other side
Subtract 4 from both sides
3x^2-5x-3
a = 3
b = -5
c = -3
Remember quadratic formula:
![x=(-b(+-)√(b^2-4ac) )/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/lavpzgggwfat6r2g7ra1ym6g07yf04d2de.png)
IGNORE THE A BEFORE THE ±
Plug in our a, b, and c values:
![x=(-(-5)±√(5^2-4(3)(-3)) )/(2(3))](https://img.qammunity.org/2023/formulas/mathematics/high-school/xuart3uzjm8bliphvk2s16ldf20sxemmtw.png)
Simplify:
![x=(5±√(25+36) )/(6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/htf0p9vopcj1sk4xfslu3eww89y2iu2pnv.png)
Simplify some more:
![x=(5±√(61) )/(6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ndv14f0g7ymhx1gga5zpd1iyuxv3uzyiqq.png)
Solve:
x ≈ -0.47
x ≈ 2.14